1983
DOI: 10.1111/j.1600-0897.1983.tb00239.x
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte Subsets Defined by Monoclonal Antibodies in Human Pregnancy

Abstract: Using monoclonal antibodies, indirect immunofluorescence, and flow cytometry, the proportions and absolute numbers of various lymphocyte subsets in peripheral blood have been measured in normal human pregnancy. Groups of ten women were studied at 12, 28, and 36 weeks of gestation and compared with 16 nonpregnant control women. The percentage of T cells (OKT3+) was constant throughout pregnancy, and this was confirmed in three women studied serially prior to and throughout early pregnancy. A slight fall in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 23 publications
(1 reference statement)
1
5
0
Order By: Relevance
“…Similar changes in B cell compartment have been reported in a number of human pregnancy studies . The absolute numbers and frequencies of circulating CD5 + B cells are decreased in normal human pregnancy (Table ), and can persist for up to 1 month postpartum .…”
Section: B Cell Alterations In Pregnancysupporting
confidence: 78%
“…Similar changes in B cell compartment have been reported in a number of human pregnancy studies . The absolute numbers and frequencies of circulating CD5 + B cells are decreased in normal human pregnancy (Table ), and can persist for up to 1 month postpartum .…”
Section: B Cell Alterations In Pregnancysupporting
confidence: 78%
“…Several studies [ 17 27 ] both prospective and cross-sectional have reported on circulating B cells during normal human pregnancy with majority describing lower total numbers and/or frequency when compared to levels post-partum or in healthy non-pregnant. Most studies [ 17 , 19 24 , 27 ] have only investigated total B cells as defined by the expression of CD20 or CD19 with older studies [ 18 , 25 , 26 ] using either expression of Ia (HLA-DR) or surface immunoglobulin. A few studies [ 17 , 19 , 24 , 27 ] have reported on the frequency of B cell subsets expressing CD5 with majority describing lower frequency or lower total numbers of this subset during pregnancy, at delivery or early in the postpartum period.…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, the overall antibody titers to influenza infection are lower in pregnant mice (Medina and Kincade, 1994;Smithson et al, 1998;Chan et al, 2010). Similar changes have also been found in humans by many studies (Christiansen et al, 1976;Moore et al, 1983;Valdimarsson et al, 1983;Iwatani et al, 1988;Watanabe et al, 1997;Mahmoud et al, 2001a). Of note, steroid hormones regulate humoral immunity at multiple stages of B cell development.…”
Section: Humoral Immune Modulations In Pregnancy That Influence Vaccimentioning
confidence: 55%